EVALUASI KINERJA GENERATOR AC SEDERHANA SECARA EKSPERIMEN BERDASARKAN VARIASI KECEPATAN PUTARAN DAN DIAMETER KAWAT - Syaukani, Muhammad; Syah, Muhammad Aksel; Arirohman, Ilham Dwi; Afisna, Lathifa Putri; Pujiyulianto, Eko (Jurnal Teknologi Terapan, 2025)
Small-scale renewable energy use is crucial for supplying the world's electrical needs. Utilizing these renewable energy sources requires a device that can transform mechanical power into electrical power. The purpose of this research is to construct a simple AC generator by converting mechanical power into electricity by varying the copper wire's diameter and rotational speed. The outcomes of the investigation include information on the electrical power, torque, mechanical power, and efficiency of the generator. The technical details of the generator employed are 12 poles, a rotor diameter of 9.25 cm, and a stator diameter of 9 cm. The results of the investigation reveal that the generator with the 0.15 mm variation in copper wire diameter performs better than the generators with the 0.75 mm variation in wire diameter. It can generate 80,6 watts of electric power, 1,231 N.m. of torque, 193,468 watts of mechanical force, and 41.66% of efficiency at a rotational speed of 1500 rpm. The result shows that the generator's performance will vary depending on the diameter of the wire at different rotating speeds.